Matrix Concept Understanding Ability: A Quantitative Descriptive Study on Grade XI Vocational High School Students - Fallo, Maria Delastrada; Son, Aloisius Loka; Maifa, Talisadika S. (Journal of Instructional Mathematics, 2022)
Understanding and completing a basic mathematical concept is often faced by students. This problem is fundamental to mathematical ability. This ability is part of the competency to understand mathematical concepts. Therefore, this study was conducted to describe the students' ability to understand matrix concepts. This study is a quantitative descriptive, be held on grade XI students from Multi Media I of a vocational high school at Kefamenanu. The number of participants in this study was 26 students. The instrument used is a test of the ability to understand the concept of the matrix and interviews. The results of this study indicate that the ability to understand the matrix concept of grade XI Multi Media I students is in the medium category with a percentage of 56.6%, with details of 7 students in the high category, 13 students in the medium category, and 6 students in the low category. There are 96% of students can restate a concept, 46% of students can classify objects according to the concept, 57% of students can give examples and non-examples of concepts, 61% of students can present concepts in various forms of mathematical representation, and 23% of students can use, utilize and select settlement procedures.